1987
DOI: 10.1172/jci113230
|View full text |Cite
|
Sign up to set email alerts
|

Human red cells scavenge extracellular hydrogen peroxide and inhibit formation of hypochlorous acid and hydroxyl radical.

Abstract: The ability of intact human red cells to scavenge extracellularly generated H202 and Oj, and to prevent formation of hydroxyl radicals and hypochlorous acid has been examined. Red cells inhibited oxidation of ferrocytochrome c by H202. Cells treated with aminotriazole no longer inhibited, indicating that protection was almost entirely due to intracellular catalase. Contribution by the GSH system was slight, and apparent only with low H202 concentrations when catalase was inhibited by aminotriazole. The cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
2
2

Year Published

1990
1990
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(84 citation statements)
references
References 24 publications
3
77
2
2
Order By: Relevance
“…Speculation that pegloticase therapy may increase H 2 O 2 to toxic levels (25) implies a greater rate of production than elimination. Before clinical testing we considered this possibility unlikely for these reasons: (i) because of PEGylation, infused pegloticase would be restricted to plasma (20); (ii) H 2 O 2 freely crosses cell membranes; and (iii) erythrocytes are known to have a prodigious capacity to decompose H 2 O 2 generated within the vascular compartment (26,27). We estimate that erythrocytes can eliminate H 2 O 2 2-3 orders of magnitude faster than it can be produced by pegloticase therapy (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Speculation that pegloticase therapy may increase H 2 O 2 to toxic levels (25) implies a greater rate of production than elimination. Before clinical testing we considered this possibility unlikely for these reasons: (i) because of PEGylation, infused pegloticase would be restricted to plasma (20); (ii) H 2 O 2 freely crosses cell membranes; and (iii) erythrocytes are known to have a prodigious capacity to decompose H 2 O 2 generated within the vascular compartment (26,27). We estimate that erythrocytes can eliminate H 2 O 2 2-3 orders of magnitude faster than it can be produced by pegloticase therapy (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…† The rate at which intact human erythrocytes scavenge extracellularly generated H 2 O 2 is based on a previous study (27), and assumes a hematocrit of 40. Effect of urate plus pegloticase on Prx2 in reconstituted blood.…”
Section: )mentioning
confidence: 99%
“…In erythrocytes, catalase is supposed to be a more predominant H 2 O 2 -removing enzyme than GPx [22][23][24] and to have an important role in the disposal of exogenous H 2 O 2 , particularly in brain, heart and skeletal muscle. 2,3) Therefore, it is likely that catalase inhibition and the resulting elevation of extracellular H 2 O 2 level by increased blood uric acid cause oxidative stress in the tissues of those patients with hyperuricemia or gout. It was reported that there was an influence regarding catalase deficiency to mental retardation in WAGR syndrome and to H 2 O 2 -caused oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…2) Intact erythrocytes are capable of protecting other cells or tissues against several injuries by extracellular H 2 O 2 . 3,4) Since H 2 O 2 readily diffuses through membranes, erythrocyte catalase is regarded as a primary enzyme for the removal of extracellular H 2 O 2 . 4,5) Therefore erythrocyte catalase may pro-reduction of erythrocyte catalase activity and the resulting increase in H 2 O 2 levels would cause cerebral disorders in patients with hyperuricemia or gout.…”
Section: Introductionmentioning
confidence: 99%
“…Predominantly, because of amphlpathic nature of H 2 0 2 , this reactive species occurring extracellularly is readily transferred across membranellipid bilayers and degraded intracellular by various cells, such as erythrocytes [12]. To elUCIdate the pathogenesis of 2-cell block, effects of SOD, catalase and erythrocytes on fertilized oocytes and embryos were studied in vitro.…”
Section: Introductionmentioning
confidence: 99%